Hydrophobic and conductive cotton fabric with silver nanowires and silanes - Nejman, Alicja; Celichowski, Grzegorz; Cieślak, Małgorzata (Wydawnictwo Politechniki Łódzkiej, 2022)
Hydrophobic and conductive cotton (CO) fabric was prepared by coating with silver nanowires (AgNWs) and mixture of two silanes: 3-aminopropyltriethoxysilane (APTES) and diethoxydimethylsilane (DEDMS). New functionalization method was developed in which the silanes mixture was applied to the previously deposited AgNWs layer. The AgNWs/silanes modified fabric showed hydrophobic properties. The water contact angle was 130 ± 1deg. The surface free energy was approximately 16 ± 1 mJ/m2, while for unmodified fabric it was 42 ± 1 mJ/m2. Unmodified fabric was nonconductive, the electrical surface (Rs) and volume (Rv) resistances was 3.9 x 1011 ± 3.4 x 1010 Ω and 2.2 x 1010 ± 1.7 x 109 Ω, respectively. After AgNWs/silanes modification it decreased to 7.5 x 102 ± 3.6 x 101 Ω and 7.0 x 102 ± 1.0 x 101 Ω, respectively. Hydrophobic and conductive cotton fabric has the potential to use in new specific purposes.
Keywords: cotton fabric; silver nanowires; silanes; hydrophobic; surface free energy; conductivity; tkanina bawełniana; nanodruty srebra; silany; hydrofobowy; swobodna energia powierzchniowa; przewodnictwo